Influence of Glutamine and Glutamate Supplementation in the Blood Levels of Horses - Cordeiro Manso, Helena Emília Cavalcanti da Costa; de Oliveira, Deyvson Ferreira; Hunka, Monica Miranda; Cordeiro Manso Filho, Hélio (Acta Scientiae Veterinariae, 2019)
Background: The most abundant free amino acid in mammals is glutamine (GLN). Little research has focused on GLN supplementation for horses, but GLN levels in this species are known to decline after exercise and during lactation. Under physiological conditions, the body produces Gln in sufficient quantities for general metabolism, and a small part of this amino acid comes from dietary protein. Little research has so far focused on equine dietary supplementation with free glutamine or combined with other amino acids during catabolic states or in highly stressful situations. This research was conducted to evaluate the effects of equine dietary supplementation using a combination of glutamine and glutamate. Materials, Methods & Results: The study involved four Arabian mares, not in training ( 380 kg; 12 years old) and four treatments (control, and inclusions of 1, 2 and 4% of GLN+GLU) in a Latin square model. A 7-day washout period was established between each phase. Fifty percent of the mares’ maintenance energy requirements came from concentrate and 50% from hay and grazing. The other 50% came from Tifton hay (Cynodon dactylon), which was supplied ad libitum. After 7 weeks of nutritional supplementation (once a day, in the morning). In the experimental model, the mares were distributed in a Latin square design comprised of four treatments: control (without inclusion) and inclusions of 1%, 2% and 4% of supplement (AminoGut®, Ajinomoto do Brazil), and four animals. Blood was collected in five stages (fasting, and 60, 120, 240 and 360 min after feeding) in each treatment. The blood samples were analyzed to determine GLN, GLU, urea, creatinine, uric acid, total plasma protein, hematocrit and glucose levels. Glutamine and Glutamate concentrations were analyzed using the enzymatic spectrophotometric method. The results were analyzed statistically using one- and two-way ANOVA and Tukey’s test with P set at 5%. The results indicated that GLN differed in both the group (P < 0.001) and between the phases of supplementation (P < 0.001), but no interaction occurred between them (P > 0.05). Significant changes in GLN levels were also observed in the 4% inclusion treatment compared to all the treatments in the fasting phase and in the + 60 min and +240 min phases of the control group (P < 0.05). All the other biomarkers analyzed here were unchanged (Glutamate, Urea, Creatinine, Urea, TPP, Glucose and Hematocrit) (P > 0.05) during the period under analysis, and remained within the normal range for the species in their current stabling conditions. The mares presented no clinical problems nor did they change their feeding behavior during the supplementation period or on the days blood was collected. Discussion: Glutamine metabolism in horses has yet to be extensively studied. However, it has been shown that, when supplied to horses in its free form, this amino acid causes Gln levels to rise rapidly within the first 90 min of the postprandial period. This indicates that an extra amount of this amino acid may increase Gln blood levels despite intense degradation of enterocytes. This study found that supplementation with a combination of Gln+Glu can increase blood Gln levels after 6 h in the treatment involving 4% Gln+Glu included in the concentrate (P < 0.05) In conclusion, supplementation with GLN+GLU raised the mares’ GLN levels after 360 min when 4% of GLN+GLU was included in their diet. These results may be used to establish GLN supplementation models for horses.